Interaction of polyethylene nanoplastics with the plasma, endoplasmic reticulum, Golgi apparatus, lysosome and endosome membranes: A molecular dynamics study - Limei Xu; Zhenyu Ma; Jingyi Zhu; Zhuo Liu; Yuyang Song; Min Xiao; Jian Li; Xukai Jiang; Lushan Wang (Ecotoxicology and Environmental Safety, 2025)
The pervasive presence of micro- and nanoplastics in the environment and their potential infiltration into the human body, has sparked significant concerns regarding their implications for human health. In this study, we utilized all-atom molecular dynamics (MD) simulations to investigate the interactions of polyethylene nanoplastics with various biological membranes, including those of the plasma, endoplasmic reticulum, Golgi apparatus, lysosomes, and endosomes. Informed by membrane lipidomics data from literature, we constructed biologically accurate structural models of these membranes. Our findings revealed that polyethylene nanoplastics interacted spontaneously with all the membranes examined. The interaction typically involved aggregation of polyethylene molecules into nanoparticles near the membrane surface, followed by adsorption, insertion, and eventual translocation into the hydrophobic core of the lipid bilayers. Through quantitative analysis of the dynamic behaviors and structural characteristics of the membranes, we observed that the insertion of polyethylene nanoplastics changed the lipid organization and inhibited membrane fluidity in most cases. These results shed light on the interactions between polyethylene nanoplastics and biological membranes, offering atomic-scale insights into the connection between nanoplastic cytotoxicity and membrane responses.